THE INFLUENCE OF ENVIRONMENTAL FACTORS IN THE PRODUCTION OF GUM ARABIC (ACACIA SENEGAL, FABACEAE) – A META-ANALYSIS. - e Silva, Thâmara Machado; de Souza, João Paulo Francisco (Revista Brasileira de Climatologia, 2018)
The gum Arabic obtained from the trunk and branches of the woody species Acacia senegal and Acacia seyal is a polysaccharide exudate with numerous biochemical properties, whose production can suffer impacts of several environmental factors. Thus, the objective of this work is to evaluate the effect of some environmental factors on the production of this exudate. For this study, we compared the production of the gum in the rainy season and the dry season through a meta-analysis, using for these purpose studies already published in several databases. To complement, a meta-regression was performed to evaluate the influence of environmental variables on the effect of rain on rubber production. We used 13 papers that met the criteria of the meta-analysis. It was possible to observe that the production of gum Arabic is higher in the rainy season when compared to the dry season. In addition, an effect of the minimum temperature and humidity of the air on the best production was noticed.